Gestational weight gain as a factor associated with urinary incontinence and quality of life - Aulia, Rizka; Sukarsa, M. Rizkar Arev; Prasetyo, Dwi; Hilmanto, Danny; Sasotya, R.M. Sonny; Susiarno, Hadi (Universitas Airlangga, 2025)
HIGHLIGHTS There is a correlation between maternal weight gain and urinary incontinence, an increase in weight during pregnancy may raise the risk of urinary incontinence. Urinary incontinence correlates with poorer quality of life in pregnant women and has the potential to affect their well-being negatively. ABSTRACT Objective: Urinary incontinence (UI) frequently occurs in pregnancy, primarily caused by increased intra-abdominal pressure. If left unmanaged, UI can lead to both physical and psychological discomfort, potentially reducing a pregnant woman’s quality of life. This research aimed to examine the relationship between gestational weight gain and the occurrence of urinary incontinence, along with its effects on quality of life. Materials and Methods: A cross-sectional study was carried out among 50 pregnant women in their third trimester residing within the working area of Lebaksiu Primary Health Care, Tegal Regency, Central Java, Indonesia. Pre-pregnancy weight was extracted from the Handbook of Maternal and Child Health (MCH), while current weight was measured directly using the validated Indonesian version of the ICIQ-UI SF questionnaire, while quality of life was assessed with the Indonesian version of the WHOQOL-BREF. Both instruments were administered through face-to-face interviews. Correlation was tested using Spearman’s rank correlation, with statistical significance set at p<0.05. Results: The results showed a statistically significant positive correlation between maternal weight gain and the incidence of urinary incontinence (p=0.001; r=0.462), and a significant negative correlation between urinary incontinence and quality of life (p=0.000; r=-0.614). Seventy percent of the pregnant women experienced urinary incontinence, and 46% reported decreased quality of life. Conclusion: These findings suggest that greater maternal weight gain is associated with a higher risk of UI, and that UI negatively affects pregnant women’s quality of life. Integrating educational programs and policies that emphasize the importance of maintaining an ideal body weight during pregnancy may help prevent UI and improve the overall quality of life for pregnant women.